Computational drug discovery for the Zika virus - Melina Mottin; Joyce Villa Verde Bastos Borba; Cleber Camilo Melo-Filho; Bruno Junior Neves; Eugene Muratov; Pedro Henrique Monteiro Torres; Rodolpho Campos Braga; Alexander Perryman; Sean Ekins; Carolina Horta Andrade (Universidade de São Paulo, 2018)
Few Zika virus (ZIKV) outbreaks had been reported since its first detection in 1947, until the recent epidemics occurred in South America (2014/2015) and expeditiously became a global public health emergency. This arbovirus reached 0.5-1.3 million cases of ZIKV infection in Brazil in 2015 and rapidly spread in new geographic areas such as the Americas. Despite the mild symptoms of the Zika fever, the major concern is related to the related severe neurological disorders, especially microcephaly in newborns. Advances in ZIKV drug discovery have been made recently and constitute promising approaches to ZIKV treatment. In this review, we summarize current computational drug discovery efforts and their applicability to discovery of anti-ZIKV drugs. Lastly, we present successful examples of the use of computational approaches to ZIKV drug discovery.